(untitled) (Dissertare, 2023)
The objective of the research was to make an approach to the thematic contributions on Digital Marketing (DM). It is a descriptive study with documentary design, based on literature review and conducted under the assumptions of qualitative methodology. The content analysis technique was used having as information units 86 scientific articles published in the period 2018-2020 and which are registered in the REDALYC database. The resulting thematic contributions emphasize aspects such as: the factors that define customer behavior, the optimal way to use information and communication technologies as a way to achieve innovation in marketing and in the organizational context in general, the impact of MD in meeting the specific requirements of populations located in public and private sectors, as well as the strategic management of resources and capabilities in the analyzed area. In conclusion, it is highlighted that the study of the thematic contributions responds to the need to know and understand the scope of DM in organizations and its implications on performance, as well as its impact on specific types of organizations.